1993
DOI: 10.1073/pnas.90.3.794
|View full text |Cite
|
Sign up to set email alerts
|

Prenyl modification of guanine nucleotide regulatory protein gamma 2 subunits is not required for interaction with the transducin alpha subunit or rhodopsin.

Abstract: Guanine nucleotide-binding regulatory protein (G protein) by dimers that were active in reconstitution assays were produced in insect cells using the baculovirus/Sf`9 insect cell expression system. Sf9 cells were infected either singly or in combination with recombinant baculoviruses containing a human G-protein .31 gene or a bovine G-protein 72 gene. It was possible to express the .i1 and 72 gene products independently of each other in this system, as determined by using immunological and metabolic labeling t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
24
2

Year Published

1994
1994
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 48 publications
1
24
2
Order By: Relevance
“…heterotrimer [31, 461. The latter findings are, however, at odds with a recent report indicating that isoprenylation of the y2 subunit is not required for the interaction of the ply2 dimer with the a subunit of retinal transducin [32]. Most interestingly, partially purified plyzC68S, a mutant plyz dimer that corresponds to the p1y1C71S dimer used in this study, failed to inhibit calmodulin-stimulated type-I adenylyl cyclase activity and did not potentiate the stimulation of type-I1 adenylyl cyclase by activated a, [31].…”
Section: Discussioncontrasting
confidence: 56%
“…heterotrimer [31, 461. The latter findings are, however, at odds with a recent report indicating that isoprenylation of the y2 subunit is not required for the interaction of the ply2 dimer with the a subunit of retinal transducin [32]. Most interestingly, partially purified plyzC68S, a mutant plyz dimer that corresponds to the p1y1C71S dimer used in this study, failed to inhibit calmodulin-stimulated type-I adenylyl cyclase activity and did not potentiate the stimulation of type-I1 adenylyl cyclase by activated a, [31].…”
Section: Discussioncontrasting
confidence: 56%
“…We confirmed that the apparent affinity for rhodopsin was Ͼ12 times higher for ␤ 1 ␥ 2 than for ␤ 1 ␥ 1 for the wild-type structures, whereas the two ␤ 1 ␥ dimers displayed no difference in affinity for retinal G␣ t . Although one study using rhodopsin to catalyze GDP/GTP exchange on the G␣ t subunit showed that the ␤ 1 ␥ 1 dimer supported a faster rate of exchange than did ␤ 1 ␥ 2 or ␤ 1 ␥ 3 (38), others have found a much lower apparent affinity for ␤ 1 ␥ 1 than for other ␤␥ dimers (20,27,30,39). The direct measurement of rhodopsin-G protein interactions using surface plasmon resonance also revealed a higher affinity of ␤ 1 ␥ 2 for rhodopsin compared with ␤ 1 ␥ 1 and showed that this difference was due to a lower dissociation rate for ␤ 1 ␥ 2 (22).…”
Section: Discussionmentioning
confidence: 99%
“…There is also ample evidence suggesting the involvement of the prenyl groups in protein-protein interactions (26 -29). Two ␤␥ dimers, ␤ 1 ␥ 1 and ␤ 1 ␥ 2 , display a Ͼ10-fold difference in their affinity for bovine rhodopsin (20,30), but no apparent difference in interaction with retinal G␣ t . Since these two ␥ subunits differ in both primary amino acid sequence and isoprenoid modification, we designed this study to examine the quantitative contributions of isoprenoid modification and protein structure to the ␤␥ dimer affinity for rhodopsin.…”
mentioning
confidence: 99%
“…Other receptor-G protein coupling studies also supported the notion that receptors can have different affinities for ␤␥ dimers. Studies of bovine rhodopsin activation of ␣ t have found differences in apparent affinity among tissue-derived ␤␥ dimers of defined compositions or recombinant ␤␥ dimers, whereas ␣ t shows essentially no preference for ␤␥ dimers (31)(32)37). The fact that both GRP-R and NMB-R preferred bovine brain ␤␥ over ␤ 1 ␥ 2 and the diverse composition of bovine brain ␤␥ dimers (37,38) suggest there may be other ␤␥ dimer(s) having higher affinity or/and efficacy than ␤ 1 ␥ 2 in enhancing the catalytic activity of GRP-R and NMB-R on G␣ q .…”
Section: Discussionmentioning
confidence: 99%